The antiviral activity of Laportea decumana methanolic extract against NDV virus - Tee, Albert; Pho, Duc Khiem; Beatrix, Musung Anastasia; Dorothy, Wijaya; Sutejo, Richard (Pharmaciana, 2024)
The avian species virus that causes Newcastle disease is an extremely contagious illness. Avian paramyxovirus 1, or Newcastle disease virus (NDV), is a virus that brings harm to poultry's central nervous system and digestive tract. The NDV outbreak was initially documented in 1928 in Java, Indonesia. Newcastle disease does not currently require therapy. One popular and useful strategy for preventing and treating viral infections, such as Newcastle disease, is vaccination. With a variety of native medicinal plants and an abundance of biodiversity, Indonesia presents a promising area for biotechnology and pharmaceutical research. Laportea decumana, is a native plant in the Eastern part of Indonesia that contains alkaloids, glycosides, steroids, flavonoids, tannin, and saponin. Its cytotoxic, analgesic, antioxidant, and antibacterial properties have all been demonstrated. The antiviral properties of L. decumana have not been extensively researched. Thus, the purpose of this study is to examine L. decumana's antiviral activity, particularly against NDV, using a variety of techniques, including the plaque assay, cytotoxicity test, and gene expression experiment. L. decumana extracts at 100 mikrogram per mL or less is a safe concentration to consider, as it still has 65 persen and above cell viability based on the results of the cytotoxic assay.